THE LIFE CYCLE OF ANTIBODY-FORMING CELLS : I. THE GENERATION TIME OF 19S HEMOLYTIC PLAQUE-FORMING CELLS DURING THE PRIMARY AND SECONDARY RESPONSES - Tannenberg, Walter J. K. (The Rockefeller University Press, 1968)
The generation, time of cells synthesizing 19S antibody was measured during the exponential phase of the primary and secondary immune responses. Using a plaque-forming cell assay together with a double label isotope method, the duration of the generation time was found to be about 13 hr, that of the S period was about 8 hr, and that of G-1 and G-2 were about 3 and 2 hr, respectively, in both immune responses. Previous work was confirmed showing that all plaque-forming cells observed during the exponential phase of the immune responses incorporate labeled thymidine, and therefore take part in proliferation. These results were obtained at points during both responses when the doubling time of the PFC was observed to be 6–7 hr. This finding makes untenable the hypothesis that the rate of appearance of PFC equals the rate of proliferation of these cells. A hypothesis is presented to account for these findings and to serve as a basis for further experiments.